A very rare case of neuroendocrine carcinoma of stomach - Abhishek Purkayastha; Neelam Sharma; Virender Suhag; Vibha Dutta (Wolters Kluwer Medknow Publications, 2016)
We report an extremely rare case of neuroendocrine carcinoma (NEC) of the stomach, which is known for its aggressive behavior and poor prognosis. To the best of our knowledge, only a few cases have been reported in the world till date and our case may be one of the very few of this rare pathology. A 42-year-old male presented with vague abdominal pain and significant weight loss. Upper gastrointestinal endoscopy revealed ulceroproliferative growth in the pylorus. Computed tomography of the abdomen showed thickening of the pylorus with locoregional lymphadenopathy. Positron emission tomography scan showed localized disease. A distal gastrectomy with D1 dissection was performed. Postoperative histopathology revealed high grade NEC of the stomach with cytokeratin-20, epithelial membrane antigen, chromogranin, and CDX-2 positivity on immunohistochemistry. He was treated with adjuvant chemotherapy followed by locoregional radiotherapy with significant response to treatment. Presently on regular follow-up without any evidence of recurrence or distant metastasis.